Gas Exchange, Stem Water Potential and Xylem Flux on Some Grapevine Cultivars Affected by Esca Disease - Andreini, L.; Caruso, G.; Bertolla, C.; Scalabrelli, G.; Viti, R.; Gucci, R. (South African Journal of Enology and Viticulture, 2016)
The effect of esca disease on gas exchange, stem water potential and xylem flux of adult grapevines of Cabernet Sauvignon, Sangiovese and Trebbiano cultivars was studied over three growing seasons. Water relations were measured at véraison and cluster ripening on three types of vines: i) healthy (control); ii) symptomatic and iii) apparently healthy in the year of measurements but that had showed esca symptoms in the previous season. Xylem flux was determined on cane segments by perfusion using a tracing dye before and after the appearance of esca symptoms. Esca induced a marked reduction (about 70%) in carbon assimilation and stomatal conductance, especially in Cabernet Sauvignon and Sangiovese. Esca did not affect the stem water potential. Gas exchange parameters measured before the symptoms appeared in plants affected by esca were similar to those of healthy plants. Measurements made one month before the appearance of the symptoms cannot be used as screening method to determine whether the vine will show esca. No differences in dye translocation were found before the symptoms’ appearance. However, a decrease in xylem flux was measured in symptomatic vines of Cabernet Sauvignon. After the appearance of esca symptoms, only the Trebbiano had a lower xylem flux than the healthy vines.